Nature, Development, and Distribution in Latin America. Evidence on the Role of Geography, Climate, and Natural Resources - Michael Gavin; Ricardo Hausmann (Inter-American Development Bank, Office of the Chief Economist, 1998)
Latin America`s enormous endowment of natural resources impacts many countries of the region. Economic liberalization in several countries was followed by rapid growth of foreign investment and exports of natural resource-intensive products. Growth of labor-intensive manufacturing industries was much more modest. What does increased reliance upon natural resource-based industries mean for development prospects, and for the distribution of income?
Keywords: 330; Entwicklung; Einkommensverteilung; Natürliche Ressourcen; Klima; Lateinamerika